Qualitative study on perception of antenatal mothers towards oral health care: In-depth interview - Ab. Halim, Noorhazayti; Md Mustafa, Md Muziman Syah; Esa, Rashidah (2018)
Introduction: Attending regular dental check-up is very important to pregnant women. However, many women do not utilize oral healthcare services during the antenatal period. It had been reported in Health Information Management System report (MOH, 2007) that the attendance of antenatal mothers to dental clinic were unsatisfactory. Therefore, the aim of this research was to explore the perception of antenatal mothers towards oral health care. Materials and method: In-depth interviews were carried out with a convenience sampling of 20 antenatal mothers across three government health clinics in Selangor, Malaysia. The interview using guided questions which explored participant’s oral health knowledge, attitude and practice. All interviews were audio recorded, transcribed verbatim and analysed by thematic analysis. The interview were carried out until the saturation of information were achieved. Results: The main themes emerging from the data related to low oral health knowledge, poor attitude and oral health practices during pregnancy. Although all participants have basic knowledge of dental caries development, however, many of them unaware of the significance of preventive dental visits during pregnancy. Poor attitudes and oral health practices among antenatal mothers in this study were due to they had not received the necessary oral health information. Conclusion: Antenatal mother’s perception of oral health care crucially impacts on oral health status, continuity of utilization of oral healthcare services and hence pregnancy outcome. Their views provided a baseline information for planning and formulating appropriate oral health education and promotion strategies.